Association of lipid-lowering drugs and antidiabetic drugs with age-related macular degeneration: a meta-analysis in Europeans : clinical science - Mauschitz, Matthias; Verzijden, Timo; Schuster, Alexander K.; Elbaz, Hisham; Pfeiffer, Norbert; Khawaja, Anthony; Luben, Robert N.; Foster, Paul J.; Rauscher, Franziska G.; Wirkner, Kerstin; Kirsten, Toralf; Jonas, Jost B.; et al. (British journal of ophthalmology, 2023)
Background/aims To investigate the association of commonly used systemic medications with prevalent age-related macular degeneration (AMD) in the general population. - Methods We included 38 694 adults from 14 population-based and hospital-based studies from the European Eye Epidemiology consortium. We examined associations between the use of systemic medications and any prevalent AMD as well as any late AMD using multivariable logistic regression modelling per study and pooled results using random effects meta-analysis. - Results Between studies, mean age ranged from 61.5±7.1 to 82.6±3.8 years and prevalence ranged from 12.1% to 64.5% and from 0.5% to 35.5% for any and late AMD, respectively. In the meta-analysis of fully adjusted multivariable models, lipid-lowering drugs (LLD) and antidiabetic drugs were associated with lower prevalent any AMD (OR 0.85, 95% CI=0.79 to 0.91 and OR 0.78, 95% CI=0.66 to 0.91). We found no association with late AMD or with any other medication. - Conclusion Our study indicates a potential beneficial effect of LLD and antidiabetic drug use on prevalence of AMD across multiple European cohorts. Our findings support the importance of metabolic processes in the multifactorial aetiology of AMD.